Importance of Prosecution Witnesses in Terrible Crimes of Sexual Violence, Abduction, Abuse, Torture, Rape And Killing Against Innocent Women and Children: Dr Aftab Ahmad Malik, Mujtaba Asad, Waqar Azeem - Dr Aftab Ahmad Malik; Mujtaba Asad; Waqar Azeem (International Journal for Electronic Crime Investigation, 2020)
The cases against innocent women and children are tremendously increasing day by day. The offenders are committing sexual intimidation and harassment accompanied by a high degree of torture and killing. The burglars are also observed in such offenses with rape, torture, and/or killing as modus-operandi. Rape is defined under ‘Hadood Laws’ in Islamic Jurisprudence and suggests strong punishments. The ‘Taazir’ sanctions sanctify emerging and contemporary types of criminality. The majority of Islamic penal law’s sentences are ‘Taazir’ in nature. The most popular forms of ‘Taazir’ include imprisonment, whipping, fines, and the death penalty. According to Islamic jurisprudence, society must protect its morals, Apart from other factors, this paper focuses on the importance of prosecution witnesses. The prosecution witnesses are the backbone of a criminal case in the court. The criminals and their alias keep following up with the witnesses to prevent and avert the evidence in court; because they know the related information and knowledge about the offense. The paper probes the psychological and psychiatric reasons, why the offenders have abnormal behavior of this type. Therefore, the protection and safe custody of witnesses is of very high importance, particularly in cases of murder and rape. We highlight the ordinary as well as expert witnesses and their role in the cases, regarding proceedings by the prosecution. The role of witnesses is of immense importance. This paper presents two case studies to justify that prosecution must build up and collect enough substantial evidence to win the case in court.